HNRNPA1, a Splicing Regulator, Is an Effective Target Protein for Cervical Cancer Detection: Comparison With Conventional Tumor Markers. Issue 2 (1st February 2017) - Kim, Young-Jon; Kim, Byoung-Ryun; Ryu, Jae-Suk; Lee, Gyeong-Ok; Kim, Hak-Ryul; Choi, Keum-Ha; Ryu, Jae-Won; Na, Kyoung-Suk; Park, Min-Cheol; So, Hong-Seob; Cho, Ji-Hyun; Park, Do-Sim
Abstract : Objective: Heterogeneous nuclear ribonucleoprotein A1 (HNRNPA1), serine/arginine-rich splicing factor 1 (SRSF1), and SRSF3 are splicing regulators associated with oncogenesis. However, the alterations of SF proteins and their diagnostic values in cervical cancer are unclear. To apply SFs clinically, effective marker selection and characterization of the target organ properties are essential. Materials and Methods: We concurrently analyzed HNRNPA1, SRSF1, SRSF3, and the conventional tumor markers squamous cell carcinoma antigen (SCCA) and carcinoembryonic antigen (CEA) in cervical tissue samples (n = 127) using semiquantitative immunoblotting. In addition, we compared them with p16 (cyclin-dependent kinase inhibitor 2A [CDKN2A]), which has shown high diagnostic efficacy in immunohistochemical staining studies and has been proposed as a candidate protein for point-of-care screening biochemical tests of cervical neoplasia. Results: HNRNPA1, higher molecular weight forms of SRSF1 (SRSF1-HMws), SRSF3, CEA, and p16 levels were higher ( P < 0.05) in cervical carcinoma tissue samples than in nontumoral cervical tissue samples. However, the levels of SRSF1-Total (sum of SRSF1-HMws and a lower molecular weight form of SRSF1) and SCCA, a commonly used cervical tumor marker, were not different between carcinoma and nontumoral tissue samples. In paired sample comparisons, HNRNPA1 (94%) showed the highest incidence of up-regulation (carcinoma/nontumor, >1.5) in cervical carcinoma, followed by p16 (84%), SRSF1-HMws (69%), SRSF3 (66%), CEA (66 %), SCCA (32%), and SRSF1-Total (31%). HNRNPA1 (92%) and p16 (91%) presented the two highest diagnostic accuracies for cervical carcinoma, which were superior to those of SRSF3 (75%), SRSF1-HMws (72%), CEA (72%), SCCA (59%), and SRSF1-Total (55%). Conclusions: Our results identified that HNRNPA1 is the best diagnostic marker among the SFs and conventional markers given its excellent diagnostic efficacy for cervical carcinoma, and it has a p16-comparable diagnostic value. We suggest that HNRNPA1 is an additional effective target protein for developing cervical cancer detection tools.